Reduction of Emergency Room Service Time at St. Carolus Summarecon Serpong Hospital, Indonesia with DMAIC Approach in 2023 - Saputera, Christina; Basabih, Masyitoh (Universitas Muhammadiyah Yogyakarta, 2025)
Service time is one of the quality ER’s indicators that is still a problem in various hospitals. This study was conducted based on the ER’s quality indicator achievement, service time ≤ 3 hours at St. Carolus Summarecon Serpong Hospital which always does not reach the target (74,3% of the target > 90% of total ER inpatients) and is reinforced by the researcher’s search in SINTA indexed journals, there has been no research discussing the ER’s service time improvement using DMAIC interventions up to the control stage. The result using operational research design, blended method and probability sampling techniques (a sample of 32 ER patients) successfully identified unplanned discharges of inpatients to cleaning service staff, room entrustment policies, waiting lists for VIP rooms, and the lack of human resources for inpatient nurses, as the root cause of the problem, reducing lead time from 4:14 to 2:39:2 (↓ 37,4%) at the post-intervention stage and to 2:19:46 (↓ 12,1%) at the control stage; reduce non value-added activities from 1:38:19 to 32:22 (↓ 67,1%) at the post-intervention stage and to 25:23 (↓ 21,6%) at the control stage and successfully eliminate waste transport, reduce waste waiting time and lead time by 55%.